IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE TO THE EIGHT GRADE STUDENTS OF SMP SWASTA KATOLIK BUDI MURNI 1 MEDAN - Damanik, Rostani; Pangaribuan, Jontra J.; Ginting, Fiber Yun A. (Kairos English Language Teaching Journal, 2020)
Reading is not only about pronouncingÂ written words correctly but also comprehending the text. It is not surprising the students have difficulties in reading comprehensionÂ because they do not understand the language. Therefore the teacher must try to help the students comprehend the text. One thing the teacher can do is to find a technique to teach this reading comprehension. Cooperative Integrated Reading and Composition can help the students to improve their reading comprehension and to arouse their motivation. The aim of this study is to find whether Cooperative Integrated Reading and Composition Technique works effectively on improving studentsâ€™ reading comprehension and to knowÂ what studentsâ€™ responsesÂ after being taught by using this technique. The subject of this study is the eighth grade students of SMP Swasta Katolik Budi Murni 1 Medan in the Academic Year of 2018/2019 were consist 25 students of class VIII C. This study was conducted by applying Classroom Action Research (CAR), which was performed in two cycles ( cycle I and cycle II). The instruments of collecting dataÂ were Quantitative data (reading comprehension test) and and qualitative data (field notes,obervation sheet,questionnaire)The result of reading comprehension tests showed that the mean of the studentsâ€™ score increased from pre-test (20 %), formative test (52 %), post-test (76 %). The field notes, observation sheet and questionnaire showed that the students are interested in the learning teaching process through CIRC Technique and this study run well. It was found that this technique could improve studentsâ€™ reading comprehension. It is suggested that English teacher should apply this technique in teaching reading comprehension.